The Flickering Global City - Eric Slater (Journal of World-Systems Research, 2015)
This article explores new dimensions of the global city in light of the correlation between hegemonic transition and the prominence of financial centers. It counterposes Braudels historical sequence of dominant cities to extant approaches in the literature, shifting the emphasis from a convergence of form and function to variations in history and structure. The marked increase of finance in the composition of London, New York and Tokyo has paralleled each citys occupation of a distinct niche in world financial markets: London is the principal center of currency exchange, New York is the primary equities market, and Tokyo is the leader in international banking. This division expresses the progression of world-economies since the nineteenth century and unfolds in the context of the present hegemonic transition. By combining world-historical and city-centered approaches, the article seeks to reframe the global city and overcome the limits inherent in the paradigm of globalization.